ULF waves observed in solar wind and on the ground at high, mid, and low latitudes. (April 2020) - Alimaganbetov, Mergen; Streltsov, Anatoly V.
Abstract: We analyze fluctuations of the magnetic field in the solar wind registered by the ACE satellite in the L1 Lagrangian point and the ULF waves observed with ground magnetometers at high, middle, and low latitudes during 84 intense substorm events. Our goal is to establish possible connections between ULF oscillations observed simultaneously in the different parts of the solar wind–magnetosphere–ionosphere system during substorms. Our analysis reveals that there is a good correlation between oscillations with frequencies less than 1 mHz observed in the solar wind and in three different latitudes during strong substorms. In particular, we show that: (1) the dominant frequencies of the waves observed on the ground at high, middle, and low latitudes are approximately the same; (2) the waves with frequencies of 0.45–0.55mHz, and 0.75–0.80mHz are the most often seen in high, middle, and low latitudes and in the solar wind. Therefore, we conclude that there is a strong coupling between the Earth's magnetosphere–ionosphere system and the solar wind in the frequency range below 1mHz mediated by the disturbances in the magnetic field. Highlights: We perform statistical analysis of the ULF waves detected during substorms in the solar wind and on the ground at high, mid, and low latitudes. We found that in 28 out of 84 considered substorm events, the waves with almost the same frequency  < 1 mHz were detected in all locations. ULF waves with frequencies 0.45–0.55mHz and 0.75–0.80mHz are common during substorms and during their respective preceding quiet times. The magnitudes of ULF waves at low latitudes are larger than the magnitudes of ULF waves at mid latitudes. The occurrence of ULF waves at middle and low latitudes correlate in time with variations in the  D s t index.